Multitargeting approaches involving carbonic anhydrase inhibitors: hybrid drugs against a variety of disorders - Claudiu T. Supuran (Taylor & Francis Group, 2021)
Carbonic anhydrases (CAs, EC 4.2.1.1) are enzymes involved in a multitude of diseases, and their inhibitors are in clinical use as drugs for the management of glaucoma, epilepsy, obesity, and tumours. In the last decade, multitargeting approaches have been proposed by hybridisation of CA inhibitors (CAIs) of sulphonamide, coumarin, and sulphocoumarin types with NO donors, CO donors, prostaglandin analogs, β-adrenergic blockers, non-steroidal anti-inflammatory drugs, and a variety of anticancer agents (cytotoxic drugs, kinase/telomerase inhibitors, P-gp and thioredoxin inhibitors). Many of the obtained hybrids showed enhanced efficacy compared to the parent drugs, making multitargeting an effective and innovative approach for various pharmacological applications.